A New Multilevel Inverter Based Grid Connected Reliable Solar Power Transfer Unit with Power Quality Enhancement - M, Nirmal Mukundan C; V., Sangeetha; P., Jayaprakash; V., Asokan O.; Al-Durra, Ahmed; Zeineldin, Hatem; EL-Fouly, Tarek H. M. (IEEE transactions on industry applications, 2023)
This article proposes a multilevel inverter (MLI) based grid-connected solar power transfer unit (PTU). This work is a technological enhancement for the interconnection of photovoltaic (PV) array and distribution grid for mitigating the present energy crisis and power quality issues. The proposed MLI generates nine-level output voltage with a minimum device count and reduced losses. Hence, it provides a low harmonic AC waveform with higher efficiency when compared to the reported topologies. The MLI configuration consists of two isolated DC sources, realized by PV array management in a ratio of 3:1. Eight switches are used in the circuit, out of them, two are bidirectional to achieve the four-quadrant operation and thereby realize the control of reactive power flow. The least number of ON-OFF transitions in high power switches are ensured to minimize the switching losses. The single-stage PTU is controlled to extract the maximum power from PV arrays at varying irradiance levels. The shunt-connected PTU is controlled with an adaptive least mean square algorithm to enhance the grid power quality by meeting the nonlinear local load demands. Three modes of PTU operation are presented in this work according to the available PV power and load power information, and the grid power quality compliance with the IEEE-519 standard is verified in each mode. Battery-supported DC bus voltage regulation is adopted to overcome the reliability issue of the solar PV array power. The proposed system is designed and simulated in MATLAB/Simulink and tested at various operating conditions. Further, the real-time system behavior is tested and validated on a hardware model.